A protocol for isolating insect mitochondrial genomes: a case study of NUMT in Melipona flavolineata (Hymenoptera: Apidae). (3rd July 2016) - Françoso, Elaine; Gomes, Fernando; Arias, Maria Cristina
Abstract: Nuclear mitochondrial DNA insertions (NUMTs) are mitochondrial DNA sequences that have been transferred into the nucleus and are recognized by the presence of indels and stop codons. Although NUMTs have been identified in a diverse range of species, their discovery was frequently accidental. Here, our initial goal was to develop and standardize a simple method for isolating NUMTs from the nuclear genome of a single bee. Subsequently, we tested our new protocol by determining whether the indels and stop codons of the cytochrome c oxidase subunit I ( COI ) sequence of Melipona flavolineata are of nuclear origin. The new protocol successfully demonstrated the presence of a COI NUMT. In addition to NUMT investigations, the protocol described here will also be very useful for studying mitochondrial mutations related to diseases and for sequencing complete mitochondrial genomes with high read coverage by Next-Generation technology.